A Study of Folklore: A Determinant of Names of the Canals:: A Determinant of Names of the Canals and Villages in Bang Bo District, Samutprakan Province - Thongkon, Wuthipong; Jamaroon, Phansiri; Kwanthong, Kodchaporn (Academic and Research Journal of Liberal Arts (Online), 2021)
This research aimed at the study of the history and some backgrounds of how to name the canals and villages along them in Bangbo District, Samut Prakan Province. It also aimed at the study of the roles and the importance of the canals that have been changing from the past to present. It is a qualitative research emphasizing on field work and documentation. Informal interviews with the elderly in the district, local scholars, community leaders and the monks were used. Moreover, the study included the government documentation: semi-academic writings, local records, memorial pamphlets of some funerals and cremations, the maps of all canals in the past and present time, looking at the physical features of the canals and related places. There was an examination of all information using “Triangulation Techniques”. It was found that most of the canals and villages in Bangbo District, Samut Prakan Province were named by people in the areas using the names of some important people living in the canals or the unique features of the canals like the names of the plants in the areas, the sizes or the directions of the canals, the topography of the areas, the animals, the structures, the behaviors, the instruments, and the beliefs or legends, respectively, to help people easily remember them for convenient communication and good understanding. Later, the roles and importance of the canals from the past to present have been changed according to the economic development of the country. The canals in the past which were critically used as the original of the community, economic areas for people to earn their living. The main communication have become the economic growth with business areas, industries, and new villages of newcomers along the roads with urbanization. The villages along the canals have been changed into semi-urban-rural societies. At present, the canals are only waterway to the seas.